1994
DOI: 10.1007/bf01416097
|View full text |Cite
|
Sign up to set email alerts
|

Net nitrogen mineralization in soils under six indigenous tree species, an abandoned pasture and a secondary forest in the atlantic lowlands of costa rica

Abstract: Nitrogen mineralization, nitrification potentials, pH, total N, C, extractable P and cations were measured in soils under 4-year-old, mono-specific stands of six fast-growing, native tree species, an abandoned pasture, and a 20-year-old secondary forest, as part of a study on the use of indigenous tree species for rehabilitation of soil fertility' on degraded pastures at the La Selva Biological Station in the Atlantic humid lowlands of Costa Rica. Soil net nitrification potential rates were higher under two N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 20 publications
2
11
0
1
Order By: Relevance
“…Response in soil-N to the presence of N 2 -fixers has been reported previously (Montagnini and Sancho 1994). Fertilization with P plus K also did not create consistent patterns in soil concentrations of these or other nutrients.…”
Section: Nutrient Cyclingmentioning
confidence: 63%
“…Response in soil-N to the presence of N 2 -fixers has been reported previously (Montagnini and Sancho 1994). Fertilization with P plus K also did not create consistent patterns in soil concentrations of these or other nutrients.…”
Section: Nutrient Cyclingmentioning
confidence: 63%
“…The lower soil pH in G?M may be due to increased soil nitrification (Binkley and Sollins 1990). Szott et al (1991) and Montagnini and Sancho (1994) also reported that incorporation of N 2 -fixing trees, such as Dalbergia, in the production system often results in increased soil N mineralization and nitrification, which leads to lower soil pH. Therefore, these results suggest that these systems of G?M, G?R?S and G?W?S significantly improved the organic matter and pH, especially in the upper soil layer, which may help in sustaining soil productivity.…”
Section: Soil Chemical Propertiesmentioning
confidence: 98%
“…However, after the bioassay, NO − 3 -N was considerably increased and NH + 4 -N decreased, suggesting that nitrification had occurred, perhaps caused by some form of incubation process in the bioassay pots. N mineralization experiments with volcanic soils in Costa Rica (Montagnini and Sancho, 1994) also revealed enhanced nitrification in incubations.…”
Section: Quinoa Biomass Production Capacity and Soil Nutrient Deficiementioning
confidence: 89%